The Formidable Double D: Analysis of Desire and Disability - Ilyes, Emese (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2018)
This article untangles the social representation of people with intellectual disabilities by calling attention to a recent story tucked in the shadowy crevices of American newspapers. These articles found on the Internet are not static presentations of facts, but rather dynamic sites of interactions where people respond, dispute, and elaborate on the content. This work traces the social origins and locations of everyday knowledge, drawing on Serge Moscovici’s social representation theory that considers knowledge to be a process that is communally enacted, socially embedded, and ongoing. An analysis of the language used by journalists and commentators on published internet articles related to the case found that individuals oppressed by the label of intellectually disabled are often prevented from defining themselves, this task is deferred to professionals and families. When a relationship is established with someone else, it is therefore assumed to be a clinical relationship. Characteristics such as inaccessibility to verbal communication lead to infantilization, which makes consent inconceivable. Finally, lurking behind these themes is the implication that people who are oppressed by the label of intellectually disabled are less than human and therefore do not have the privilege of inalienable human rights, such as the right to feel desire.